FACTORS ASSOCIATED WITH FAMILY PLANNING ACCEPTORS' DECISIONS IN CHOOSING INTRAUTERINE DEVICES (IUD) AT THE PEUKAN BADA COMMUNITY HEALTH CENTER, ACEH BESAR DISTRICT - Maulizananda, Putri; Adamy, Aulina; Menawati, Menawati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: The low utilization of intrauterine contraceptive devices (IUCDs) in the community is influenced by various factors. This study aimed to identify factors associated with the decision of family planning acceptors in choosing IUCDs. Method: The study employed a descriptive analytic approach with a case-control design. The population consisted of 3.315 women of reproductive age (WRA), with a sample of 60 cases and 60 controls. Data were collected through interviews using a structured questionnaire. Result: The results showed significant associations between IUCD selection and several variables: age (p = 0.001; OR = 2.7), education (p = 0.003; OR = 3.2), occupation (p = 0.003; OR = 3.4), number of children (p = 0.006; OR = 2.3), knowledge (p = 0.009; OR = 2.8), income (p = 0.014; OR = 2.8), attitude (p = 0.005; OR = 3.0), husband's support (p = 0.003; OR = 3.2), access to family planning services (p = 0.010; OR = 2.8), and information availability (p = 0.002; OR = 3.5). In contrast, health facility availability (p = 1.000; OR = 0.8) and distance (p = 4.231; OR = 0.001) showed no significant association with IUCD selection. Recommendation: Based on these findings, it is recommended that family planning programs strengthen community education, enhance male partner involvement, ensure the quality of family planning services, and improve access to accurate and comprehensible information to support informed contraceptive choices and increase IUCD utilization.